1
$\begingroup$

I want to prove $ (\frac{n}{e})^n \leq n! \leq en ( \frac{n}{e})^n$ by induction. For this prove I want to use the inequality $(\frac{n+1}{n})^n < e <(\frac{n+1}{n})^{n+1}$.

for $n=1$ the inequality is obvious. I Assume it is true for a fixed $n\in \mathbb{N}$ and want to show that $ (\frac{n+1}{e})^{n+1} \leq (n+1)! \leq e(n+1) ( \frac{n+1}{e})^{n+1} $

However I have problems with using both the induction hypothesis and the inequalities $(\frac{n+1}{n})^n < e <(\frac{n+1}{n})^{n+1}$ to obtain my answer.

$\endgroup$
0
$\begingroup$

Using the mentioned inequality we have:

$$\left(\frac{n+1}{n}\right)^n < e \implies \frac{(n+1)^n}{e^{n+1}} < \frac{n^n}{e^n} \implies \left(\frac{n+1}{e}\right)^{n+1} < \left(\frac{n}{e}\right)^n(n+1) \le n!(n+1) = (n+1)!$$

This proves the left side of the inequality. Similarly:

$$e < \left(\frac{n+1}{n}\right)^{n+1} \implies n\left(\frac{n}{e}\right)^n < \left(\frac{n+1}{e}\right)^{n+1}$$

Using this and the induction hypothesis we have:

$$e(n+1)\left(\frac{n+1}{e}\right)^{n+1} > (n+1)en\left(\frac{n}{e}\right)^n \ge (n+1)n! = (n+1)!$$

Hence the inequality is proven

$\endgroup$
0
$\begingroup$

I had originally written this up for another question but it seems fitting here as well. Maybe this can help someone.

Depending on how you introduced $e$, you might be able to use the fact that there are two sequences $(a_n)_{n \in \mathbb{N}}$, $(b_n)_{n \in \mathbb{N}}$ with

$$\begin{align} a_n ~~~&:=~~~ \left ( 1 + \frac{1}{n} \right ) ^n \\ ~ \\ b_n ~~~&:=~~~ \left ( 1 - \frac{1}{n} \right ) ^{-n} \end{align}$$

and

$$\underset{n \rightarrow \infty}{\lim} a_n ~~~=~~~ \underset{n \rightarrow \infty}{\lim} b_n ~~~=~~~ e \\ ~ \\$$

While both sequences converge to the same limit, $a_n$ approaches from the bottom and $b_n$ approaches from the top:

import numpy as np
import matplotlib.pyplot as plt
from matplotlib import rcParams
rcParams.update({'figure.autolayout': True})

pts = np.arange(0, 20, 1)
a_n = lambda n: (1+1/n)**n
b_n = lambda n: (1-1/n)**(-n)

plt.errorbar(x = pts, xerr = None, y = a_n(pts), yerr = None, fmt = "bx", markersize = "5", markeredgewidth = "2", label = "$a_n$")
plt.errorbar(x = pts, xerr = None, y = b_n(pts), yerr = None, fmt = "rx", markersize = "5", markeredgewidth = "2", label = "$b_n$")
plt.plot(pts, [np.exp(1)]*len(pts), color = "black", linewidth = 2, label = "$e$")
plt.xlim(1.5, 14.5)
plt.ylim(2.0, 3.5)
plt.legend(loc = "best")
plt.setp(plt.gca().get_legend().get_texts(), fontsize = "22")
plt.show()

So we're going to use the following inequality:

$$\forall n \in \mathbb{N} ~ : ~~~~~ \left ( 1 + \frac{1}{n} \right ) ^n ~~~~<~~~~ e ~~~~<~~~~ \left ( 1 - \frac{1}{n} \right ) ^{-n} \tag*{$\circledast$} \\ ~ \\$$


Thesis

$$\forall n \in \mathbb{N}, ~ n \geq 2 ~ : ~~~~~ e \cdot \left ( \frac{n}{e} \right )^n ~~~~<~~~~ n! ~~~~<~~~~ n \cdot e \cdot \left ( \frac{n}{e} \right )^n \\ ~ \\$$


Proof By Induction

Base Case

We begin with $n = 2$ and get

$$\begin{align} & ~ && e \cdot \left ( \frac{2}{e} \right )^2 ~~~~&&<~~~~ 2! ~~~~&&<~~~~ 2 \cdot e \cdot \left ( \frac{2}{e} \right )^2 \\ ~ \\ & \Leftrightarrow && e \cdot \frac{4}{e^2} ~~~~&&<~~~~ 1 \cdot 2 ~~~~&&<~~~~ 2 \cdot e \cdot \frac{4}{e^2} \\ ~ \\ & \Leftrightarrow && \frac{4}{e} ~~~~&&<~~~~ 2 ~~~~&&<~~~~ \frac{8}{e} \\ ~ \\ &\Leftrightarrow && 2 ~~~~&&<~~~~ e ~~~~&&<~~~~ 4 ~~~~ \\ \end{align} $$

Which is a true statement.

Inductive Hypothesis

Therefore the statement holds for some $n$. $\tag*{$\text{I.H.}$}$

Inductive Step

$$\begin{align} & ~ && e \cdot \left ( \frac{n+1}{e} \right )^{n+1} \\ ~ \\ & = && (n+1) \cdot \frac{1}{e} \cdot e \cdot \left ( \frac{n+1}{e} \right )^n\\ ~ \\ & = && (n+1) \cdot \left ( \frac{n}{e} \right )^n \cdot \left ( \frac{n+1}{n} \right )^n\\ ~ \\ & = && (n+1) \cdot \left ( \frac{n}{e} \right )^n \cdot \left ( 1 + \frac{1}{n} \right )^n\\ ~ \\ & \overset{\circledast}{<} && (n+1) \cdot \left ( \frac{n}{e} \right )^n \cdot e\\ ~ \\ & \overset{\text{I.H.}}{<} && (n+1) \cdot n!\\ ~ \\ & = && (n+1)!\\ ~ \\ & = && (n+1) \cdot n!\\ ~ \\ & \overset{\text{I.H.}}{<} && (n+1) \cdot n \cdot e \cdot \left ( \frac{n}{e} \right )^n\\ ~ \\ & = && (n+1) \cdot e \cdot \left ( \frac{n}{e} \right )^{n+1} \cdot e \\ ~ \\ & = && (n+1) \cdot e \cdot \left ( \frac{n+1}{e} \right )^{n+1} \cdot \left ( \frac{n}{n+1} \right )^{n+1} \cdot e \\ ~ \\ & = && (n+1) \cdot e \cdot \left ( \frac{n+1}{e} \right )^{n+1} \cdot \left ( 1 - \frac{1}{n+1} \right )^{n+1} \cdot e \\ ~ \\ & \overset{\circledast}{<} && (n+1) \cdot e \cdot \left ( \frac{n+1}{e} \right )^{n+1} \cdot \left ( 1 - \frac{1}{n+1} \right )^{n+1} \cdot \left ( 1 - \frac{1}{n+1} \right )^{-(n+1)} \\ ~ \\ & = && (n+1) \cdot e \cdot \left ( \frac{n+1}{e} \right )^{n+1} \\ ~ \\ \end{align} $$

Conclusion

Therefore the statement holds $\forall n \in \mathbb{N}, ~ n \geq 2$. $$\tag*{$\square$}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.